2020
DOI: 10.1108/jea-09-2019-0158
|View full text |Cite
|
Sign up to set email alerts
|

Commonplace and common language: Kentucky's district mission statements

Abstract: PurposeWe sought to identify codes and themes in the mission statements of Kentucky's school districts and examine the relationship between district characteristics and the mission statements.Design/methodology/approachWe undertook a mixed methods design, specifically, a sequential transformative strategy with a theoretical lens overlaying the sequential procedures and guiding the analysis.FindingsAnalysis revealed a range of 1–7 codes per mission statement and a mean of 3.05. Generic student success and indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Mission statements, in one study, showed themes and context driven by state and national policies (Ingle et al, 2020), with the possibility a similar conclusion could be drawn here with topics of lifelong learning, staff quality, and social-emotional learning. Gareis (1996) found citizenship to be most important and academics to be fifth, though the present study and most others found academics at the top.…”
Section: Mission Statement Meta-synthesissupporting
confidence: 61%
See 1 more Smart Citation
“…Mission statements, in one study, showed themes and context driven by state and national policies (Ingle et al, 2020), with the possibility a similar conclusion could be drawn here with topics of lifelong learning, staff quality, and social-emotional learning. Gareis (1996) found citizenship to be most important and academics to be fifth, though the present study and most others found academics at the top.…”
Section: Mission Statement Meta-synthesissupporting
confidence: 61%
“…Gareis (1996) found citizenship to be most important and academics to be fifth, though the present study and most others found academics at the top. The change could be, as Ingle et al (2020) found, the national push for academic success from No Child Left Behind could have crowded out other themes. Some studies have been difficult to compare, such as Boerema (2006), as the study looked at broad themes of a school's distinctive beliefs and listing of goals and objectives.…”
Section: Mission Statement Meta-synthesismentioning
confidence: 99%
“…The context for district leaders’ work also influences how they interpret and enact their ethical position. Mission statements and priorities for Superintendents may be similar in widely varying contexts ( Ingle et al, 2020 ; Bredeson et al, 2011 ) but actual practices vary widely and are attuned to specific community characteristics ( Bredeson et al., 2011 ; Coviello & DeMatthews, 2021 ). Finally, contexts create ethical demands: Alsbury & Whitaker (2007) found that superintendents viewed accountability, democratic community, and social justice as competing goals in their setting, which required them to use their knowledge of and relationships within their district context to weave them together in their practice.…”
Section: Ethical Educational Leadershipmentioning
confidence: 99%
“…Subsequent studies have set on similar paths though with varying geographical scope and units of analysis. Schafft and Biddle (2013) focused on school districts in Pennsylvania; Ingle et al (2020) focused on school districts in Kentucky; and Slate et al (2008) focused on schools in Texas.…”
Section: Research On School Mission Statementsmentioning
confidence: 99%
“…Charter schools are public schools that have been exempted from certain state and local regulations and which as such can pursue distinct educational objectives (National Charter School Resource Center [NCSRC], 2023). In addition, previous studies have often used mixed methods designs, with the initial stage consisting of qualitative coding for the occurrence of a theme and the later stage consisting of quantitative analyses of bivariate association or logistic regression (Ingle et al, 2020;Schafft & Biddle, 2013;Stemler et al, 2011). This kind of coding captures only the presence (''1'' yes or ''0'' no) of a theme, as opposed to its prevalence within a statement, and is limited by the coders' ability to read through a bounded number of documents.…”
Section: Introductionmentioning
confidence: 99%